Full-Tree Biomass, Root Carbon Stock, and Nutrient Use Efficiency Across Ages in Eucalyptus Stands Under Seedling and Coppice Systems - de Oliveira, Gardenia Gonçalves [UNESP]; Queiroz, Túlio Barroso [UNESP]; Bullock, Bronson P.; Coelho, José Carlos [UNESP]; Hakamada, Rodrigo Eiji; Guerrini, Iraê Amaral [UNESP] (MDPI, 2025)
The establishment of forest stands after harvest requires an understanding of biomass and nutrient dynamics to support management decisions and ensure system productivity and sustainability. This study evaluated biomass and nutrient accumulation in Eucalyptus urophylla aged 2 to 5 years under planting and coppicing systems. A total of 1152 trees were assessed across eight treatments, combining four ages and two management systems. Aboveground biomass was estimated using 10 trees per treatment, while root biomass was assessed in 8 trees at ages 3 and 5. Nutrient concentrations were determined using three intermediate-diameter class trees per treatment. Biomass data were analyzed using Tukey's test (5%), and biomass expansion factors (BEF) and the root-to-shoot ratio (R) were used to estimate root carbon. Total biomass was higher in the coppicing system (153 Mg ha-1) compared to the planting system (119 Mg ha-1), with greater root accumulation and carbon sequestration (≈17.2 t C ha-1). The biological use coefficient (BUC) increased with age, except for Mn. Planted stands showed higher BUC for N and P, while coppiced stands were more efficient in Mg use. These results reinforce the need for distinct fertilization strategies for each system, aiming at productivity, nutrient efficiency, and carbon stock enhancement.